Isolated Rectal Metastases from Locally Advanced Carcinoma Prostate Detected by 18F-PSMA-1007 PET/CT - Singh, Shashank Shekhar; Singh, Rani Kunti Randhir; Kumar, Narvesh; Atrey, Harshvardhan (World Journal of Nuclear Medicine, 2022)
Rectal involvement by prostate carcinoma is rare and isolated rectal metastases are even rarer with only a few cases having been reported in the literature. In our knowledge, no case of isolated rectal metastases diagnosed on prostate specific membrane antigen positron emission tomography/computed tomography has been reported to date. We present a case of a 66-year-old patient who presented with rectal bleeding and passage of urine from anal region and was diagnosed with carcinoma prostate infiltrating the rectum along with solitary rectal metastases.
Keywords: carcinoma prostate; rectal metastases; 18F-PSMA-1007 PET/CT